Efficacy of Sertraline Plus Placebo or Add-On Celecoxib in Major Depressive Disorder: Macrophage Migration Inhibitory Factor as a Promising Biomarker for Remission After Sertraline—Results From a Randomized Controlled Clinical Trial - Simon, Maria S.; Burger, Bianka; Weidinger, Elif; Arteaga-Henríquez, Gara; Zill, Peter; Musil, Richard; Drexhage, Hemmo A.; Müller, Norbert (Frontiers in Psychiatry, 2021)
Introduction. Previous research delivers strong indications that inflammatory activation leads to treatment resistance in a subgroup of patients with Major depressive disorder. Thus, tailored interventions are needed. The present study aimed to find potential biomarkers that may enable patients to be stratified according to immune activation. Methods. A phase IIa randomized placebo-controlled trial was performed to assess levels of inflammatory compounds in responders/remitters and non-responders/non-remitters to sertraline plus celecoxib (n=20) and sertraline plus placebo (n=23). Levels of macrophage migration inhibitory factor, neopterin, and tumor necrosis factor alpha were determined by enzyme-linked immunosorbent assay; response and remission were measured by reduction of the Montgomery Åsberg Depression Rating Scale score. Results. Both treatment groups showed a significant decline in depression symptoms but no difference was found between groups. A clear pattern emerged only for macrophage migration inhibitory factor: placebo remitters showed significantly lower baseline levels than non-remitters (a similar trend was seen in responders and non-responders) while celecoxib responders showed a trend for higher baseline levels than non-responders. Conclusion. Small subsample sizes are a notable limitation, wherefore results are preliminary. However, the present study provides novel insights by suggesting macrophage migration inhibitory factor as a promising biomarker for treatment choice.